2021
DOI: 10.1073/pnas.2021219118
|View full text |Cite
|
Sign up to set email alerts
|

Declining greenness in Arctic-boreal lakes

Abstract: The highest concentration of the world’s lakes are found in Arctic-boreal regions [C. Verpoorter, T. Kutser, D. A. Seekell, L. J. Tranvik, Geophys. Res. Lett. 41, 6396–6402 (2014)], and consequently are undergoing the most rapid warming [J. E. Overland et al., Arctic Report Card (2018)]. However, the ecological response of Arctic-boreal lakes to warming remains highly uncertain. Historical trends in lake color from remote sensing observations can provide insights into changing lake ecology, yet have not been e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 142 publications
2
29
1
Order By: Relevance
“…With the rise in LAI, a larger foliage of leaves lowers the radiation contact with bare ground surfaces and restricts soil evaporation, but increases the re-evaporation precipitation intercepted by leaves; thus, high greening can alter net evaporation. Due to intense greening, a significant increase in terrestrial evapotranspiration was observed, suggesting an intensified water exchange between land and atmosphere as feedback proportional to greening and browning as supported by various previous studies (Zhang et al, 2015;Zeng et al, 2017;Zeng et al, 2018b;Xu et al, 2020;Abbas et al, 2021;Kuhn and Butman, 2021). The overall phenomenon leads to a greeninginduced ET enhancement that increases atmospheric water vapor content and promotes downwind precipitation.…”
Section: Impact Of Lulcc On Precipitationsupporting
confidence: 63%
“…With the rise in LAI, a larger foliage of leaves lowers the radiation contact with bare ground surfaces and restricts soil evaporation, but increases the re-evaporation precipitation intercepted by leaves; thus, high greening can alter net evaporation. Due to intense greening, a significant increase in terrestrial evapotranspiration was observed, suggesting an intensified water exchange between land and atmosphere as feedback proportional to greening and browning as supported by various previous studies (Zhang et al, 2015;Zeng et al, 2017;Zeng et al, 2018b;Xu et al, 2020;Abbas et al, 2021;Kuhn and Butman, 2021). The overall phenomenon leads to a greeninginduced ET enhancement that increases atmospheric water vapor content and promotes downwind precipitation.…”
Section: Impact Of Lulcc On Precipitationsupporting
confidence: 63%
“…In particular, rainfall during the week prior to 5 August 2019 was five times higher than the average weekly rainfall during the period of beaver occupation in the Swan Lake Creek drainage (Figure 10b). Observations of failure of the dam complex and initiation of the beaver-induced permafrost degradation feature following record rainfall has implications for the ongoing rapid expansion of beavers [37,44,47] in an Arctic that is experiencing hydrologic intensification [68,69]. With the more than doubling in beaver ponds on the Seward Peninsula between 2000 and 2020 [46], the likelihood of more widespread beaver-induced permafrost degradation associated with dam failures due to an increase in extreme precipitation events has increased in the 21st Century [70].…”
Section: Discussionmentioning
confidence: 99%
“…The next generation of carbon monitoring will capture the complex linkages between WC systems, e.g. the linked permafrost and boreal lake carbon cycle [414][415][416]. As we address these challenges and opportunities, our ability to understand WC storage and fluxes will improve, and in turn, our understanding of how these ecosystems function, allowing for sustainable management and conservation.…”
Section: Recommendationsmentioning
confidence: 99%